TIMP Loss Activates Metalloproteinase‐TNFα‐DKK1 Axis To Compromise Wnt Signaling and Bone Mass. (4th October 2018) - Chen, Yan; Aiken, Alison; Saw, Sanjay; Weiss, Ashley; Fang, Hui; Khokha, Rama
ABSTRACT: Deregulated proteolysis invariably underlies most human diseases including bone pathologies. Metalloproteinases constitute the largest of the five protease families, and the metzincin metalloproteinases are inhibited by the four tissue inhibitors of metalloproteinase called TIMPs. We hypothesized that Timp genes are essential for skeletal homeostasis. We bred individual Timp knockout mice to generate unique mouse models, the quadruple Timp null strain (QT) as well as mice harboring only a single Timp3 allele (QT3 +/– ). QT mice are grossly smaller and exhibit a dramatic reduction of trabeculae in long bones by μCT imaging with a corresponding increase in metalloproteinase activity. At the cellular level, Timp deficiency compromised differentiation markers, matrix deposition and mineralization in neonatal osteoblasts from calvariae, as well as the fibroblastic colony‐forming unit (CFU‐F) capacity of bone marrow–derived stromal cells. In contrast, we observed that osteoclasts were overactive in the Timp null state, consistent with the noted excessive bone resorption of QT bones. Immunohistochemistry (IHC) and immunofluorescence (IF) analyses of bone sections revealed higher Cathepsin K and RANKL signals upon Timp loss. Seeking the molecular mechanism, we identified abnormal TNFα bioactivity to be a central event in Timp ‐deficient mice. Specifically, TNFα triggered induction of the Wnt signaling inhibitor Dkk1 in the osteoblasts at the mRNA and protein levels, with a simultaneous increase in RANKL. Neutralizing TNFα antibody was capable of rescuing the induction of Dkk1 as well as RANKL. Therefore, the generation of novel Timp ‐deficient systems allowed us to uncover the essential and collective function of TIMP proteins in mammalian long‐bone homeostasis. Moreover, our study discovers a functional TIMP/metalloproteinase‐TNFα‐Dkk1/RANKL nexus for optimal control of the bone microenvironment, which dictates coexistence of the osteoblast and osteoclast lineages. © 2018 American Society for Bone and Mineral Research.